Wordplay and metalinguistic/metadiscursive reflection : authors, contexts, techniques, and meta-reflection - Winter-Froemel, Esme; Zirker, Angelika (Dynamics of wordplay ;, 2015)
This volume is the first of two bringing together selected contributions from linguistics and literary studies focusing on the variegated manifestations of wordplay in different communicative settings. By investigating basic techniques and ludic traditions, the volumes offer a fresh look on the metalinguistic/metadiscursive dimension of wordplay as well as on its various kinds of interplays.